PELATIHAN PENCATATAN KEUANGAN SEDERHANA DAN MENGENALKAN FINANCIAL LITERACY PADA PERSERTA DIDIK SMKN 6 KOTA SERANG - Latif, Latif; Novitasari, Sela; Maryati, Maryati; Novriansyah, Wahyu (Yayasan Education and Social Center, 2024)
This community service activity aims to increase financial understanding and literacy among students at SMKN 6 Serang City, with a focus on simple financial recording procedures that can be applied in everyday life. One of the main obstacles in implementing this activity is the low level of students' knowledge regarding financial management and recording. To overcome this problem, training is carried out by combining lecture methods and direct practice, so that students can understand theory and directly apply the material in a relevant context. At the end of the activity, it is hoped that the participants will not only have a basic understanding of financial recording, but will also be able to implement these skills in their personal lives or even in running their small businesses in the future. In this way, they will be better prepared to face the challenges of managing their finances well and effectively, and can develop healthy financial habits from an early age